Groove pancreatitis: a brief literature review (Brazilian Journal of Health Research, 2023)
Introduction: Groove pancreatitis is a rare kindt of chronic pancreatitis, which affects a virtual space entitled pancreatic groove. The exact etiology is still unknown, but it shows a strong association with alcoholism and smoking. The clinical and radiological presentation is similar to the pancreatic adenocarcinoma, which is important to consider for the differential diagnosis. Objectives: The purpose of this study was to review and describe clinical, radiological and anatomopathological characteristics that allow the physician to obtain knowledge about this rare disease. Methods: Systematic literature review. Results: Groove pancreatitis is more prevalent in men, aged 40 to 50 years, presenting with weight loss, abdominal pain and signs of duodenal obstruction. Radiological images show a solid lesion occupying the space between the duodenum and the pancreas, mimicking a tumor. In the endoscopy the groove pancreatitis is observed as a lesion infiltrating the duodenum, thickening and scarring of the duodenal wall, associated with stenosis and cystic formations. The anatomopathological images show fusiform stromal cells, foam cells and cell debris in granular form. Conclusion: Groove pancreatitis is a rare disease still unknown to the medical team. The diagnosis is possible with a multidisciplinary analysis of its clinical, radiological and pathological characteristics, avoiding more invasive surgical approaches.
Keywords: Groove pancreatitis; Chronic pancreatitis; Pancreatic adenocarcinoma; Paraduodenal pancreatitis